2001
DOI: 10.1097/00000542-200101000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drugs Used for Neuropathic Pain Management on Tetrodotoxin-resistant Na+Currents in Rat Sensory Neurons

Abstract: Less negative membrane potential and repetitive firing have little effect on tetrodotoxin-resistant Na(+) current amplitude but increase their sensitivity to lidocaine, mexiletine, and amitriptyline so that concentrations after intravenous administration of these drugs can impair channel function. This may explain alleviation from pain by reducing firing frequency in ectopic sites without depressing central nervous or cardiac excitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 0 publications
5
54
0
2
Order By: Relevance
“…Pharmalogical studies show that amitriptyline acts at Na ϩ Ch, diazepam and midazolam at BDZ-Rs, gabapentin at GABA A -R and L-Ca 2ϩ Ch ␣2␦-1 (42), and carbamazepine at Na ϩ Ch (43). Our present findings show that these receptors and ion channels are strongly up-regulated.…”
Section: Identification Of Differentially Expressed Genes and Verificsupporting
confidence: 62%
“…Pharmalogical studies show that amitriptyline acts at Na ϩ Ch, diazepam and midazolam at BDZ-Rs, gabapentin at GABA A -R and L-Ca 2ϩ Ch ␣2␦-1 (42), and carbamazepine at Na ϩ Ch (43). Our present findings show that these receptors and ion channels are strongly up-regulated.…”
Section: Identification Of Differentially Expressed Genes and Verificsupporting
confidence: 62%
“…This concentration was specifically chosen, because it has been demonstrated that the half-maximum inhibitory concentration values for lidocaine to block tetrodotoxin-resistant (TTX-R) Na ϩ channels, and thereby inhibiting nerve conduction in rat sensory neurons, were 73 mol/L and 128 mol/L, respectively. 17,18 Lidocaine completely reversed the HFES-induced increase of GAP-43 levels and neurite outgrowth ( Figure 2B and 2C).…”
Section: Hfes Of Nigp Induced Neuronal Growthmentioning
confidence: 88%
“…Although epinephrine and norepinephrine have previously been shown to sensitize nociceptors located on small diameter primary afferents in the periphery (Hu and Zhu 1989;Khasar et al 1999b;Shyu et al 1989), elevated levels of central catecholamines are generally associated with descending inhibition of pain via actions at α 2 ARs or D 2 DARs in the spinal dorsal horn (Millan 2002). Antidepressants used extensively in the treatment of persistent pain conditions, are thought to inhibit pain transmission at the spinal level by increasing synaptic levels of norepinephrine and serotonin (Sanchez and Hyttel 1999) as well as by blocking tetrodotoxin-resistant sodium channels (Brau et al 2001). Furthermore, catecholamine-induced elevations in blood pressure have been shown to produce analgesia through the stimulation of arterial baroreceptors Randich and Maixner 1984;Zamir and Maixner 1986).…”
Section: Comt Inhibition Increases Pain Behavior Via β 2 and β 3 Adrementioning
confidence: 99%